Integrasi Filsafat Pendidikan Islam dan Tantangan Karakter dalam Masyarakat 5.0 - Andrian Al Firdaus; Ahmad Faqih Alawi; Alfiah Wanda Vinita (At-Tafakkur: Journal of Islamic Studies, 2025)
The emergence of Society 5.0 presents new challenges in character formation, particularly in relation to moral decline, technological disruption, and shifts in social behavior. In Islamic education, character development is not merely a matter of social ethics but an integral part of tarbiyah, ta’dib, and the cultivation of akhlaq. This article aims to analyze the integration of Islamic philosophy of education with the challenges of character formation in the Society 5.0 era. This study employs a library research approach by examining the philosophical perspectives of Muslim scholars such as Al-Ghazali, Ibn Miskawaih, and Syed Muhammad Naquib al-Attas, and exploring their relevance to contemporary social dynamics. The findings indicate that core values in Islamic education—such as tauhid, fitrah, akhlaq, and the balance between reason and revelation—can serve as foundational principles to address moral disorientation in the digital era. The philosophy of Islamic education also emphasizes that character formation must be rooted in spirituality, moral literacy, and exemplary conduct. This integration provides an alternative framework for Islamic education in responding to the challenges of Society 5.0 in a substantive and sustainable way. Therefore, the Islamic philosophy of education is not only relevant but also strategic as an approach to reconstructing human character amid technological acceleration and socio-cultural transformation.